Prevalence of poor sleep quality in athletes before competition - Andrade, A.; Bevilacqua, G. G.; De Orleans Casagrande, P.; Brandt, R.; Coimbra, D. (The Physician and Sportsmedicine, 2021)
Objectives The purpose of this study was to investigate athletes sleep quality before competition and its relationship with age, gender, sport modality, competitive level, competition result, and practice time.